If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 9 = 23 + -4x Reorder the terms: 9 + 4x = 23 + -4x Solving 9 + 4x = 23 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 9 + 4x + 4x = 23 + -4x + 4x Combine like terms: 4x + 4x = 8x 9 + 8x = 23 + -4x + 4x Combine like terms: -4x + 4x = 0 9 + 8x = 23 + 0 9 + 8x = 23 Add '-9' to each side of the equation. 9 + -9 + 8x = 23 + -9 Combine like terms: 9 + -9 = 0 0 + 8x = 23 + -9 8x = 23 + -9 Combine like terms: 23 + -9 = 14 8x = 14 Divide each side by '8'. x = 1.75 Simplifying x = 1.75
| -16t^2+33t+3=19 | | 4x+33=13-39 | | 600=40x | | A-4b=3 | | -2a+3b=14 | | 2(x-1)=2x-10 | | y+(-3)+7=0 | | log^4(9x+19)=3 | | y+(-3)+7= | | X+.1x=487771 | | Y=1+4y^2 | | 6-2(x+6)=9-5(x+3) | | 4(9x-12)=3(16x-12) | | 3[2x-1]+5=14 | | 1/4(16x-20)=1/5(25x-20) | | 1/4(16x-20)=1,5(25x-20) | | A=3a+t-2g | | 4[2x+1]=36 | | 7x+5=8(x-6) | | 5(x-3)+2=3(x+2) | | b/12-6=6 | | 2(4x+10)=17x-43 | | 6x^2+16=0 | | 3(u+7)-7u=37 | | 5y-2x=25 | | 3+(u+7)-7u=37 | | a(3+4)=4 | | 4a(3+4)= | | (25-3x)=(3x-17) | | 13-9x=101-37 | | 25-5y=4x-9y+13 | | 15x-90=180 |